Penguatan Pengetahuan Kimia Siswa MA Sakti Ngebel Ponorogo melalui Praktikum Kimia Berbasis Fun Chemistry Learning dalam Mendukung Pendidikan Berkualitas - Ade Trisnawati; Sudarni, Dyan Hatining Ayu; Prasongko, Agung; Nisa, Halisa Khoirun; Berliansyah, Victora Aulian; Mukhorobin, Achmad Zakiy Afif; Yudhistira, Yansi Ferdiana (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
MA Sakti Ngebel, a secondary education institution in Ngebel District, Ponorogo Regency, has excellent potential to develop more context-based chemistry learning. MA Sakti students have previously struggled to understand fundamental chemistry concepts, particularly in relating them to everyday phenomena. Students tend to memorize formulas without understanding the meanings and applications of the concepts. Therefore, an effort is needed to implement simple, applicable, and school-specific learning innovations. One relevant approach is the implementation of Fun Chemistry Learning based chemistry practicums. The purpose of this community service (PKM) activity is to strengthen the understanding of chemistry concepts at MA Sakti Ngebel Ponorogo through FCL-based chemistry practicums. The stages of this PKM activity are program socialization, training, implementation of FCL learning innovations, mentoring, evaluation, and program sustainability. The N-gain analysis of the pretest and posttest results indicates that the increase in students’ knowledge of chemistry concepts falls in the moderate range. The results of the overall satisfaction questionnaire showed that the lowest level of satisfaction was in the aspect of time management and events during the PKM activities (45% of students considered it very satisfactory), while the highest level of satisfaction was in the aspect of motivation to learn chemistry after the PKM activities and the effectiveness of the FCL training carried out (both of which 70% of students considered it very satisfactory).